PROGRAM PEMBERDAYAAN USAHA KECIL MENENGAH (UKM) JAMAAH LIL-MUQORROBIEN UNTUK MENINGKATKAN PEREKONOMIAN - Nur Wakit (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
Community empowerment is a social action in which the population as a community organizes itself in making collective planning and action to solve social problems or meet the needs in accordance with the capabilities and resources it has.SWOTAnalysis is a form of analysis within the management of the company or within the organization that systematically can help in the effort of preparation of a mature plan to achieve goals, both short-term and long-term goals, By using swot analysis method, the number of pilgrims who have been empowered based on age 30-35 years as many as 7 people by 25%, 36-40 years as manyas 10 people by 35%, 41-45 years as much as 1 person by 3%, 46-50 years as many as 5 people by 17%, 51-55 years as many as 2 people by 7%, 56-60 years as much as 1 person by 3%, age 61-65 years as many as 3 people by 10%. It can be concluded that most of the pilgrims who are empowered by the Commitment of the Bureau of Uswatan are 36-40 years old by 35%.